Extension of internet access to VANET via satellite receive–only terminals. (12th December 2013) - Aslam, Baber; Wang, Ping; Zou, Cliff C.
The biggest challenge, to extend Internet connectivity to vehicular ad hoc networks (VANETs), is the requirement of pervasive fully networked roadside infrastructure. This requirement is difficult to achieve especially during the initial deployment phase of vehicular networks and also in the areas where roadside infrastructure is scarce. This makes solutions that are solely dependent on roadside infrastructure impracticable. Other solutions using cellular networks or symmetric satellite communication are either expensive or do not provide sufficient bandwidth and also make the transition to mature VANET difficult during later stages. We present a solution that complements the existing ones without requiring a fully networked roadside infrastructure. The solution uses satellite receive–only terminals and very few (widely spaced) roadside units to provide pervasive Internet connectivity. The solution is cost effective, incremental and practical. We present several different design options that can be used according to a given environment.